2022
DOI: 10.18495/comengapp.v11i2.402
|View full text |Cite
|
Sign up to set email alerts
|

Automated Continuous IoT-based Monitoring System for Vaname Shrimp Cultivation Management

Abstract: Shrimp cultivation in Indonesia has been increasing since the introduction of white leg shrimp or often known as vaname (Penaeus vannamei) from the South Pacific waters. The use of a cultivation model with a circular pond with a diameter of 10 meters has begun to attract shrimp farmers in the northern coastal areas of Java, including Tuban Regency. There are several water quality parameters that affects survival rate such as Dissolved Oxygen (DO), Temperature, and Total Dissolved Solids (TDS). Shrimp pond farm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…The research results show that the developed device can operate automatically dan the data from the sensor are stored on the server. Furthermore, the researcher developed a device to monitor the quality of the shrimp ponds, with parameters including Dissolved Oxygen (DO), temperature, and TDS (Total Dissolve Solid) [13]. The research result indicated that the calibrated sensor results, analyzed using a linear regression method, had an average reading error of up to 14% for the DO sensor, and 1% for the temperature and TDS.…”
Section: Introductionmentioning
confidence: 99%
“…The research results show that the developed device can operate automatically dan the data from the sensor are stored on the server. Furthermore, the researcher developed a device to monitor the quality of the shrimp ponds, with parameters including Dissolved Oxygen (DO), temperature, and TDS (Total Dissolve Solid) [13]. The research result indicated that the calibrated sensor results, analyzed using a linear regression method, had an average reading error of up to 14% for the DO sensor, and 1% for the temperature and TDS.…”
Section: Introductionmentioning
confidence: 99%